Study of Color Rendering Evaluation Method of Light Sources for Printing Matter - Hu, Xiaojie; Lian, Yusheng; Liu, Zilong; Wei, Xianfu; Liu, Fangxi; Jin, Yang; Liu, Yanxing; Huang, Min (IEEE access, 2020)
Based on the optimization of color samples, we have developed a method to evaluate light sources' color rendering of printing matter. By performing Affinity Propagation (AP) Clustering Algorithm on the color appearance and spectra of the color printing atlas samples printed by a press, two typical color sample sets are obtained. The optimized color sample (OCS) set consists of these two typical color sample sets and it is presented by CMYK dot area coverage. The color rendering indexes (CRIs) CIE-R a , CRI2012, CIE-R f of 90 light sources are calculated by taking the OCS set, color printing atlas and standard color sample (SCS) set of CRI as the test color sample (TCS) set. By comparing the Absolute Difference (AD), Mean Absolute Difference (MAD), Coefficient of Variation (CV) and Spearman Correlation Coefficient (SCC) of the CRIs, we find that the indexes calculated by OCS set are closer to these indexes calculated by color printing atlas than by SCS set. Therefore, the OCS set is more suitable for printing applications. After output from a press and measured spectra, the OCS set with CMYK dot area coverage can be used as the TCS set to evaluate the color rendering of light sources for all printing matter output from this press. For proving the reliability of the results, that is, the universality of the OCS set to the presses, the OCS set with fixed CMYK dot area coverage is output from an another press and CRIs are calculated. The results show that OCS set we developed is better than the SCS set. This method can be used for color rendering evaluation of light sources for printing matter.